2019
DOI: 10.9734/cjast/2019/v35i530198
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Bio-fungicides (Trichoderma spp and Pseudomonas fluorescens) on Seedling Emergence, Vigour and Health of Infected Chilli Seeds (Capsicum annuum) by Colletotrichum capsici

Abstract: Damping off and fruit rot caused by Colletotrichum capsici are the major constraints in production and marketability of chilli. Systemic fungicides are commonly used to control this disease. However, continuous use of chemical fungicides leads to negative impact on environment, soil and human health. Therefore, present studies (blotter and pot experiment) were conducted to explore the bio-fungicides (as an alternative to chemical fungicide) in comparison with carbendazim using chilli seeds infected with Collet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Several other bioagents have been studied in relation to their antifungal activity against Colletotrichum as well as their efficacy to control anthracnose disease on chili pepper. The use of Trichoderma viridae and Pseudomonas fluorescens individually or in combination significantly lowers the anthracnose disease incidence (Reddy et al, 2011). An antagonistic yeast, Pichia guilliermondii strain R13, was reported to reduce the disease incidence of anthracnose in chili pepper incited by C. truncatum as low as 6.5% (Chanchaichaovivat et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several other bioagents have been studied in relation to their antifungal activity against Colletotrichum as well as their efficacy to control anthracnose disease on chili pepper. The use of Trichoderma viridae and Pseudomonas fluorescens individually or in combination significantly lowers the anthracnose disease incidence (Reddy et al, 2011). An antagonistic yeast, Pichia guilliermondii strain R13, was reported to reduce the disease incidence of anthracnose in chili pepper incited by C. truncatum as low as 6.5% (Chanchaichaovivat et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies indicated that T. viride and P. fluorescens are very effective in inhibiting mycelial growth of the pathogen [91]. It is suggested that the use of T. viride and P. fluorescens individually or in combination known to significantly lower the anthracnose disease incidence and should be used as an alternative to chemical control [92].…”
Section: Biological Controlmentioning
confidence: 99%